Architectures for open access hotspots - Paiva, António Rafael C. (2004)
This article envisages the study of wireless access points in an open access configuration. In this configuration, the users of the service have access to the network without the need of authentication and without accounting their access. Therefore, we intend to consider the particularities of an access perspective of this kind. Various technological possibilities to the wireless access network are presented and analyzed. The problem of economical sustainability of this service is also addressed. Finally, we also present two possibilities of implementation of this configuration considering two different situations for usage.